Permasalahan Hukum Keluarga Islam Kontemporer di Negara Muslim - Masyhadi Masyhadi (LP3M STITNU AL HIKMAH MOJOKERTO, 2020)
The application of Islamic family law in the decision-making process at the Court is always a problem, because the references used by the Court are always diverse, consisting of various fiqh books from various schools of thought, which results in the emergence of a variety of Court decisions on similar cases. This is very worrying for legal officials, especially from the Supreme Court and the Ministry of Religion. With the enactment of the Compilation of Islamic Family Laws the legal vacuum has been filled, and the concerns of legal officials have been resolved. This study aims to explain the problems in contemporary Islamic family law in Muslim countries. This research method is carried out by literature study with the type of descriptive-analysis research. The results of this research in the preparation of Islamic family law have a transformation process that can be used as a guide.